Analisa Model Struktur Geologi Untuk Menduga Air Tanah Dengan Menggunakan Metode Geolistrik - Azhar Adi Darmawan; Chairil Saleh; Ernawan Setyono; Andi Syaiful Amal (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Gondanglegi Kulon Village is located in Gondanglegi District, Malang Regency, the research location is in the Muhammadiyah Entrepreneur Islamic Boarding School area. From the results of information from local villagers, it was explained that in the study area there was no shallow groundwater found. This is also reinforced by the fact that there are no wells in the settlements of the residents around the Entrepreneur Muhammadiyah Islamic Boarding School, so that practically no residents use wells to fulfill clean water, they still depend on river water or PDAM services which are relatively expensive and continuous. still below expectations. As a center for religious education, Islamic boarding schools continue to develop supporting facilities. One of the most needed facilities is the availability of clean water. Quantitatively, the supply from the PDAM is not sufficient and the operational costs borne by the manager are too high. The use of groundwater is a solution that can be used to meet the needs of clean water at the research location. Therefore we need a technology to identify the point of exploration, the technology used in this research is geoelectric resistivity. By using the resistivity geoelectric method, it is expected to know the rock structure at the research location and see the potential for deep groundwater. Thus, the hope that in the future the Entrepreneur Muhammadiyah Islamic Boarding School (PPEM) will no longer depend on water raw materials from the PDAM, so the hope is that daily operational costs related to clean water needs can be minimized. From the results of the analysis and discussion, 2 (two) points of drilling recommendations were obtained, but with technical and non-technical considerations, exploration was suggested at point 3 with a potential of 4.2423 L / sec. Where at this location is a rock lithological arrangement consisting of a top soil layer, a clay layer, a tuff layer, a sandy silt layer, a sand layer and a gravel layer.